Development and application of pumped storage power generation system - Liu Zhengye (E3S Web of Conferences)
As one of the most crucial energy storage facilities in modern times, pumped storage technology utilizes the principle of gravitational potential energy and mechanical energy conversion of water to pump energy facility when the eelectric load is low, and release water to generate power when it is high. The technology mainly includes pumping pump, turbine and generator and other equipment, through the two stages of pumping and power generation cycle, to realize the storage and release of electric energy. Pumped storage power generation technology has the advantages of large scale, high efficiency, clean and environmental protection, and is widely used in power systems with stability and reliability, but it is still limited by geographical factors. With the use of clean energy and the growth of electricity demand on the electricity side, pumped storage power generation technology will continue to innovate and develop, and become an important part of energy facility in the future electricity system.